Free and Bioavailable Vitamin D Levels of Patients with Type 1 Diabetes Mellitus and Association with Bone Metabolism - DİNÇER YAZAN, CEYDA; ŞİRİKÇİ, ÖNDER; HAKLAR, GONCAGÜL (My University, 2022)
Aim Vitamin D deficiency is known to be associated with metabolic bone diseases. The aim of this study is to evaluate vitamin D and calculated free and bioactive vitamin D levels of type 1 diabetic patients and to evaluate the association with bone turnover markers. Method This cross-sectional study includes 60 patients admitted to endocrinology outpatient clinic with diagnosis of type 1 diabetes mellitus and 60 controls. Weight, height and waist circumference were recorded and blood samples were taken for measurement of 25-hydroxyvitamin D (25(OH)D), vitamin D binding protein (VDBP), osteocalcin, bone alkaline phosphatase (bone-ALP), c-telopeptide. Free and bioavailable vitamin D levels were calculated with formula. Results Vitamin D levels of type 1 diabetic patients were significantly higher (p = 0.01). Parathormone levels of the group with vitamin D level under 20 ng/ml was significantly higher (p = 0.029). VDBP levels were similar in both groups. Correlation analysis of free and bioavailable vitamin D level with osteocalcin, c-telopeptide, bone alkaline phosphatase revealed only a weak significant correlation between free vitamin D and osteocalcin (r = -0.201; p = 0.028). A negative correlation was determined between 25(OH)D and parathormone levels (r = -0.294; p < 0.005). Serum osteocalcin, bone alkaline phosphatase and c-telopeptide levels of control group were significantly higher. Conclusion 25(OH)D levels of the study population was extremely low. The measurement of VDBP and calculated free and bioactive vitamin D levels did not show a better correlation with bone turnover markers according to 25(OH)D levels.
Keywords: Tıp; Sağlık Bilimleri; Dahili Tıp Bilimleri; İç Hastalıkları; Endokrinoloji ve Metabolizma Hastalıkları; Medicine; Health Sciences; Internal Medicine Sciences; Internal Diseases; Endocrinology and Metabolic Diseases; ENDOKRİNOLOJİ VE METABOLİZMA; Klinik Tıp; Klinik Tıp (MED); ENDOCRINOLOGY & METABOLISM; CLINICAL MEDICINE; Clinical Medicine (MED); Endocrinology; Endocrine and Autonomic Systems; Endocrinology, Diabetes and Metabolism; Life Sciences; VDBP; Free vitamin D; Bioavailable vitamin D; Type 1 DM; D-BINDING PROTEIN; MINERAL DENSITY; SERUM; FRACTURES; TURNOVER; HEALTH; WOMEN